Development of ELISA against milk haptoglobin for diagnosis of subclinical mastitis in goats - Windria, Sarasati (Heliyon, 2021)
The study described the development of a haptoglobin-based diagnostic tool for mastitis in Ettawa crossbreed goats. Fifty eight milk samples were collected from a flock of goats in Yogyakarta, Central Java, Indonesia. All samples were tested for mastitis using the California Mastitis Test (CMT), Somatic Cell Count (SCC), and Polymerase Chain Reaction (PCR) to identify Staphylococcus aureus, Streptococcus uberis and Streptococcus agalactiae. The presence of haptoglobin mRNA and proteins in the milk somatic cells was detected using Sanger sequencing and SDS-PAGE, respectively. Milk haptoglobin levels were subsequently estimated using an indirect enzyme-linked immunosorbent assay (ELISA) developed in this study. The Receiver Operating Characteristic (ROC) analysis was performed to compare the sensitivity and specificity of CMT, SCC, and the ELISA using the PCR as the reference standard. Kappa test was used to determine the agreement between the three imperfect tests. Results indicated that somatic cells of goat milk expressed a haptoglobin mRNA with a size of 174 bp and two haptoglobin proteins with molecular weights of 18 kDa and 32 kDa. The PCR test showed that 81% of samples were diagnosed positive for mastitis. At a specificity level of 50%, the ROC indicated that the ELISA was more sensitive compared to SCC or CMT (consecutively, 96%, 94%, and 92%). Kappa values between haptoglobin ELISA and CMT or SCC were high (0.84 and 0.81, respectively). This study indicates that somatic cells of goat milk were capable of synthesizing and secreting haptoglobin. Milk haptoglobin can be a potential target for an early detection of mastitis in goats.